Rayleigh-Taylor instability with self-generated magnetic field and thermal conduction in 2D - Modica, F.; Plewa, T.; Zhiglo, A.V. (Вопросы атомной науки и техники, 2012)
High energy density laboratory experiments on Rayleigh-Taylor instability (RTI) [1] in nonlinear regime show the plasma behavior significantly different from classical simulation results. We include the effects of self-generated magnetic field and heat conduction in simulations aiming to improve agreement with experiments. We find maximum magnetic fields generated ~11MG (β=0.091) without heat conduction (κ=0), field growth saturated by t=20ns; and ~1.7 MG with heat conduction taken into account. Strong magnetic fields in κ=0 simulations affect flow dynamics, new modes are generated. Effect of weaker magnetic fields in simulations with physical values of κ is insignificant; the main difference with classical RTI simulations is suppressed small scale features. In none of the simulations are mass extensions observed.